1998
DOI: 10.1139/e98-002
|View full text |Cite
|
Sign up to set email alerts
|

Biostratigraphy of the Vendian-Cambrian Sukharikha River section, northwestern Siberian Platform

Abstract: The Sukharikha River section contains more than 800 m of fossiliferous Vendian and Lower Cambrian carbonate rock deposited in ramp, shelf, and slope environments. A diverse fauna of small shelly fossils, calcibionts, brachiopods, trilobites, and archaeocyaths has allowed us to develop a multi-taxa biostratigraphic framework for this section. A dearth of distinctive fossils low in the Sukharikha Formation prevents us from determining the position of the Vendian-Cambrian boundary. Abundant small shelly fossils a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…2). Archaeocyaths were also reported from the basal Pestrotsvet Formation at Selinde in the southeastern Siberian Platform (Korshunov, Repina & Sysoev, 1969;Khomentovsky & Karlova, 2002) and the uppermost Sukharikha Formation in the Igarka region of the northwestern margin of the Siberian Platform , but see Luchinina et al 1997 andRowland et al 1998). In the latter two localities, carbonates display δ 13 C oscillations with high positive peaks characteristic of the lower Tommotian boundary beds, although the position of these peaks with respect to this boundary has been questioned (Kouchinsky et al 2001(Kouchinsky et al , 2005(Kouchinsky et al , 2007.…”
Section: A3 Archaeocyaths and Other Probable Aspicular Spongesmentioning
confidence: 86%
See 1 more Smart Citation
“…2). Archaeocyaths were also reported from the basal Pestrotsvet Formation at Selinde in the southeastern Siberian Platform (Korshunov, Repina & Sysoev, 1969;Khomentovsky & Karlova, 2002) and the uppermost Sukharikha Formation in the Igarka region of the northwestern margin of the Siberian Platform , but see Luchinina et al 1997 andRowland et al 1998). In the latter two localities, carbonates display δ 13 C oscillations with high positive peaks characteristic of the lower Tommotian boundary beds, although the position of these peaks with respect to this boundary has been questioned (Kouchinsky et al 2001(Kouchinsky et al , 2005(Kouchinsky et al , 2007.…”
Section: A3 Archaeocyaths and Other Probable Aspicular Spongesmentioning
confidence: 86%
“…2). Pentactines of Sulugurella sulugurica Fedorov in Pel'man et al 1990 were originally attributed to the Calcarea and reported from the Nochorojcyathus sunnaginicus Zone of the Tommotian (Pel'man et al 1990) and from the probably slightly older uppermost Sukharikha Formation of the Sukharikha River section (Rowland et al 1998), but their hexactinellid affinity is more plausible (A. Zhuravlev, pers.…”
Section: A2 Calcareansmentioning
confidence: 99%
“…One of these sections at the northwestern margin of the Siberian platform is exposed from 67 • 12.516 N, 87 • 21.567 E (see arrow A in Fig. 1) along ∼ 3 km upstream the Sukharikha River, a right tributary of the Enisej River Rowland et al 1998; Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Tannuolina sp., halkieriid sclerites, Torellella, and the micromolluscs Aldanella and Bemella (Rowland et al, 1998; see also Kouchinsky et al, 2010). Similar shelly fauna occur through the Sellick Hill Formation on the Fleurieu Peninsula (WANG/WANG-S and SHL/FTL)…”
Section: Shiyantou Carbon Isotope Excursion "Shice"mentioning
confidence: 80%